2019
DOI: 10.4236/ojcd.2019.94009
|View full text |Cite
|
Sign up to set email alerts
|

Foot Care Practices among Type 2 Diabetics Mellitus Patients Attending Diabetes Clinics in Embu County, Kenya

Abstract: Diabetes mellitus has become a global epidemic of 21st century with disproportionately high socioeconomic burden in the developing world. Foot ulcerations secondary to peripheral neuropathy and peripheral vascular disease have led to devastating health outcomes including amputations. A descriptive survey targeting a sample size of 301 was drawn from the selected health facility. Majority of the respondents were female and aged between 40 and 70 years old. The duration that a patient had lived with diabetes, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…However, Mbisi et al reported a higher number of patients (63.3%) use a moisturizing cream on their feet daily and a few patients (5.4%) use a moisturizing cream between their toes daily. 23 This might be due to a few patients in Mbisi et al’s study has an informal education (18.2%) compared to this study where 39.2% of the patients cannot read and write.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…However, Mbisi et al reported a higher number of patients (63.3%) use a moisturizing cream on their feet daily and a few patients (5.4%) use a moisturizing cream between their toes daily. 23 This might be due to a few patients in Mbisi et al’s study has an informal education (18.2%) compared to this study where 39.2% of the patients cannot read and write.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, 1.7% of the patients were reported to wear slippers most of the time. 23 The difference might be due to the age difference of patients between the studies, where most of the patients from the Kenyan study were elders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mbisi et al [42] conducted a descriptive study to assess foot care practices among people with diabetes in five hospitals in Kenya. The study reported moderate foot care practices by calculating the sum of activities practiced by the participants.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 For instance, in Embu and Meru Counties in Kenya, 45.1% to 51.2% of diabetes patients had poor levels of foot self-care practices which were associated with a high prevalence of diabetic foot ulcers. 29 , 30 In addition, a qualitative study highlighted that delay in the presentation of diabetic foot complications is associated with a low level of knowledge and awareness of foot problems, poor health-seeking behaviours and competing for personal priorities. 31 Importantly, even when the patient visits the hospital early, only 58% of health facilities in Kenya offer diabetes care services, of which only 74% can test blood glucose.…”
Section: Introductionmentioning
confidence: 99%